Comparison of The Performance of Cultivated Kappaphycus alvarezii Seaweed at Kertasari and Tua Nanga Beaches, West Sumbawa - Anugrah, Anasta Rais; Marzuki, Muhammad; Lumbessy, Salnida Yuniarti (Jurnal Biologi Tropis, 2024)
One of the seaweed-producing areas that has considerable potential in West Sumbawa Regency is Kertasari Village and Tua Nanga Village. One type of seaweed cultivated in these two locations is the Kappaphycus alvarezii type. The success of K. alvarezii production activities is largely impacted by the selection of the proper place. The purpose of this study is to assess the performance of seaweed grown using the basic peg method at Kertasari Beach and Nanga Old Beach. This study is an experimental study using a Complete Randomized Design (RAL) with two treatments and 30 replicates. The treatment that was tested was different cultivation locations, namely P1 (Kertasari Beach) and P2 (Nanga Old Beach). Maintenance is carried out for 45 days with the basic staking method and the initial seedling weight is 100 g. The following parameters were measured: absolute weight, specific growth rate, carrageenan randement, biomass production, chlorophyll content, and water quality. The data were examined using the T test with a 95% confidence level. The results showed that cultivating K. alvarezii with basic peg motede for 45 days on Kertasari beach was the best treatment because it increased the absolute weight of K. alvarezii by 45.83 g, the specific growth rate of 0.81%/day, the carrageenan content of 37%, and biomass production of 1.51 kg/m2.